(untitled) (Bangladesh Journal of Neurosurgery, 2022)
Background: Guillain-Barre syndrome (GBS) is the leading cause of acute flaccid paralysis in children. This study was aimed to compare the clinical spectrum and shortterm outcome of children with acute inflammatory demyelinating polyradiculoneuropathy (AIDP) and acute motor axonal neuropathy (AMAN) subtypes of GBS in children. Methods: The study was a prospective cohort study done in a tertiary neurology hospital for 3 years. Children under 18 years of age fulfilling the Brighton diagnostic criteria for GBS were enrolled in the study. Based on the nerve conduction study, patients were subclassified as AIDP, AMAN, AMSAN, and others. Finally, a comparison was done in children with AIDP and AMAN subtypes. Results: A total of 102 children have fulfilled the Brighton diagnostic criteria of GBS during that study period. Among them, 83 children were included in the final analysis as NCS findings suggestive of AIDP and AMAN were found in 29(28.43%) and 54(52.94%) of cases respectively. No patient died in this cohort and follow-up was done at 3 months after discharge. A comparison of clinical data between the two groups revealed similar clinical features in most of the cases. The mean age difference between the two groups was statistically significant and AIDP was found to be more frequent in the 1-5 years age group. There was a significant association between gastroenteritis and AMAN subtypes. On symptom analysis, pain and tingling sensation were found predominantly in AMAN subtypes. Children having AMAN variants developed respiratory distress more than AIDP. Assisted ventilation were needed in 14.45% of cases and the majority of them were from the AMAN group. The mean duration of hospital stay and the mean disability scores at three months after discharge were significantly higher in the AMAN group. Conclusions: AMAN was the commonest GBS subtypes in children. AIDP was more frequent in the younger age group. Children with AMAN appeared to have higher short-term morbidity and slower recovery than those with AIDP. Bang. J Neurosurgery 2022; 11(2): 94-100